0669 Prevalence and Correlates of Nightmares in Active Duty Service Members. (12th April 2019) - Pruiksma, Kristi Ensor; Slavish, Danica; Wardle, Sophie; Ojeda, Alyssa; Taylor, Daniel; Peterson, Alan; Kelly, Kevin; Maur, Douglas; Mintz, Jim; Litz, Brett; Borah, Elisa; Brundige, Antoinette; et al.
Abstract: Introduction: Among active duty service members (SMs), little research has examined the prevalence and correlates of nightmares. The current study aims to expand this research and determine the prevalence and correlates of nightmares in 4, 119 United States Army personnel scheduled for deployment. Methods: Active-duty SMs were recruited at unit-level briefings during pre-deployment processing between November 2010 and June 2011 and completed the following measures: Beck Depression Inventory, Beck Anxiety Inventory, PTSD Checklist-Civilian (which contained the question about nightmare severity), Patient Health Questionnaire, Insomnia Severity Index, Childhood Trauma Questionnaire, Interpersonal Support Evaluation List-Short Form, State Trait Anger Expression Inventory State Anger Scale. Results: Results indicated that 1642 SMs (39.9%) reported experiencing nightmares. Those with nightmares reported greater mean levels of anxiety symptoms (3.62 vs. 11.26), depression symptoms (4.74 vs. 11.60), PTSD symptoms (22.01 vs. 40.39), insomnia symptoms (5.57 vs. 10.35), anger (13.00 vs. 17.20), physical health symptoms (3.05 vs. 5.91), and number of previous deployments (0.96 vs. 1.39). Those with nightmares also had increased odds of having clinically significant anxiety (OR = 7.15, p < .001), depression (OR = 5.57, p < .001), PTSD (OR = 12.83, p < .001), and insomnia (OR = 5.44, p < .001), as well as elevated odds of having experienced emotional abuse (OR = 2.25, p < .001), physical abuse (OR = 1.99, p < .001), sexual abuse (OR = 1.82, p < .001), emotional neglect (OR = 1.81, p < .001) and physical neglect during childhood (OR = 1.82, p < .001). Conclusion: Results indicate that nightmares are associated with increased risk for a number of adverse mental and physical health outcomes. These findings highlight the debilitating nature of nightmares in active duty service members and underscore the need for effective treatment options. Support (If Any): Funding for this work was made possible by the U.S. Department of Defense through the U.S. Army Medical Research and Materiel Command, Congressionally Directed Medical Research Programs, Psychological Health and Traumatic Brain Injury Research Program awards W81XWH-08-02-109 (Alan Peterson), W81XWH-08-02-0110 (Douglas Williamson), and W81XWH-08-02-0114 (Brett Litz).